Analysis of Patient Examination Results with Clinical Symptoms of Gonorrhea Using Microscopic Examination at Puskesmas Dasan Agung - Widyastini, Ni Komang Ari Santi; Zaetun, Siti; Agrijanti, Agrijanti; Rohmi, Rohmi (Poltekkes Kemenkes Mataram, 2024)
Tropical clinical symptoms of gonorrhea occur in men, to confirm a clinical diagnosis then use microscopic examination with gram coloring. The Puskesmas of Dasan Agung became a reference to the inspection of the STI in the city of Mataram. The purpose of this study is to identify clinical symptoms and results of microscopic examination using gram coloring. This type of research is descriptive observational which aims to know or describe the picture of a disease based on direct observation objectively. The population in this study were all patients who came with symptoms that lead to sexually transmitted diseases in January - March, totaling 13 respondents. Sampling was done by non-random purposive sampling method. This research was conducted at the Dasan Agung Health Center laboratory. The results of a study of 13 patients with clinical symptoms of STI obtained 13 positive respondents (100%) identified Neisseria gonorrhoeae. 10 male patients (67.9%) and 3 female patients (23.1%) were identified with heterosexual sexual orientation in 10 cases and 3 were homosexual.